Community based soil conservation as basis for land reclamation in the Eastern Cape - Laker, M.C. (Michiel Christiaan), 1939- (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Land-use planning))--University of Pretoria, 2006.